2013
DOI: 10.1371/journal.pone.0082280
|View full text |Cite
|
Sign up to set email alerts
|

High Nasopharyngeal Carriage of Non-Vaccine Serotypes in Western Australian Aboriginal People Following 10 Years of Pneumococcal Conjugate Vaccination

Abstract: BackgroundInvasive pneumococcal disease (IPD) continues to occur at high rates among Australian Aboriginal people. The seven-valent pneumococcal conjugate vaccine (7vPCV) was given in a 2-4-6-month schedule from 2001, with a 23-valent pneumococcal polysaccharide vaccine (23vPPV) booster at 18 months, and replaced with 13vPCV in July 2011. Since carriage surveillance can supplement IPD surveillance, we have monitored pneumococcal carriage in western Australia (WA) since 2008 to assess the impact of the 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Results from adult populations in high income countries demonstrate reduced vaccine-serotype carriage where paediatric immunisation has been programmatically introduced. 29 , 30 , 60 , 61 However, in some cohorts from low income countries, the effect on even paediatric circulating serotypes has been suboptimal, demanding better vaccination coverage and time to eradicate PCV serotype circulation. 62 It may therefore be useful for a longitudinal study to be conducted investigating colonisation in the elderly in the context of childhood vaccination programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from adult populations in high income countries demonstrate reduced vaccine-serotype carriage where paediatric immunisation has been programmatically introduced. 29 , 30 , 60 , 61 However, in some cohorts from low income countries, the effect on even paediatric circulating serotypes has been suboptimal, demanding better vaccination coverage and time to eradicate PCV serotype circulation. 62 It may therefore be useful for a longitudinal study to be conducted investigating colonisation in the elderly in the context of childhood vaccination programmes.…”
Section: Discussionmentioning
confidence: 99%
“…This has, however, been accompanied by a concurrent increase in non-vaccine serotype carriage in vaccinated children and adults, resulting in relatively unchanged overall carriage prevalence . 11 , 17 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…As expected, the widespread use of PCV in more recent years has altered serotype prevalence in carriage. Surveillance of pneumococcal carriage in Aboriginal people in Western Australia from 2008 to 2011 found a 7 % prevalence in 7vPCV serotypes across varying age groups, with serotypes 19A, 16F and 6C the most common in children under five years old [ 32 ]. Further shifts in serotype distribution and a reduction in carriage of 19A have been reported following the switch to PCV13 in 2011 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Isolates were selected based upon antimicrobial susceptibility profiles with approximately half from Aboriginal and half from non-Aboriginal children. As serotype 19A is commonly associated with serotype replacement following 7vPCV introduction [ 31 ], twelve 19A isolates from this study and six 19A isolates collected in Kalgoorlie during 2008 as part of pneumococcal surveillance in Western Australian Aboriginal people [ 32 ] were also analysed by MLST.…”
Section: Methodsmentioning
confidence: 99%
“…The Hib vaccine has no effect on other H. influenzae types, leaving high carriage rates of H. influenzae also after Hib vaccine introduction. The effect on incidence of pneumococcal carriage of the PCVs differs between studies, but an increase of non-vaccine types in nasopharyngeal carriage has been observed ( 4 ).…”
Section: Effects Of Two Bacterial Vaccines Included In the Childhood mentioning
confidence: 99%